Effect of non-ionic surfactants to the Al(III)-morin complex and its application in determination of Al(III) ions: A preliminary study - Suah F.B.M.; Ahmad M.; Mehamod F.S. (Malaysian Society of Analytical Sciences, 2024)
Indexed by Scopus